2007
DOI: 10.1111/j.1525-1438.2007.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative profile of the prevalence and age distribution of human papillomavirus type 16/18 infections among three states of India with focus on northeast India

Abstract: Human papillomavirus (HPV) DNA in cervical scrape samples of married women from Manipur (n= 692) and Sikkim (n= 415) in northeast India was determined and compared with that of women from West Bengal (n= 1112) in eastern India by polymerase chain reaction. HPV prevalence was lower in Manipur (7.4%) than in Sikkim (12.5%), which was closely followed by West Bengal (12.9%). HPV18 was predominant in Manipur (2.03%) and strikingly lower (0.2%) in Sikkim and West Bengal (0.9%), while the reverse was true for HPV16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,. 2012) [23] .…”
Section: ) the Statistical Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,. 2012) [23] .…”
Section: ) the Statistical Analysissupporting
confidence: 60%
“…2012) [23] . In Manipur, a neighboring state of Assam, lower HPV prevalence has been observed than our study [20] .From these observations it is evident that, there is quite a high percentage of HPV prevalence in the general population of Karnataka in comparison with the studies conducted in India as well as studies of global HPV prevalence. Our study is comparable to that of Uttar Pradesh.…”
Section: ) the Statistical Analysiscontrasting
confidence: 41%
“…Estimated 1,32,000 new cases and 74,000 deaths occur every year due to cervical cancer in India. 1 Sexually transmitted infection with human papilloma virus (HPV) is a precursor to the development of carcinoma cervix. Its prevalence increases due to multiple sexual partners and poor genital hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…2 With the estimated 132000 new cases and 74000 deaths every year, India accounts for one-fifth of the case in world. 3 Among all major female genital malignancies, cancer cervix is largely preventable because it has pre-invasive and a micro-invasive stages that can be detected early by screening and then effectively treated. However, competing health care priorities, insufficient financial resources, weak health systems, and limited numbers of trained providers have made high coverage for cervical cancer screening in most low-and middle-income countries difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%